Implementing Operational Risk Management in Small-Scale Agribusiness: Evidence From Alfagro, a Youth-Based Farming Enterprise - Raihan Syakira; Lokita Rizky Megawati; Rizal Sjarief Sjaiful (Indonesian Journal of Accounting, Risk and Governance, 2026)
Background: Agribusiness, particularly in small-scale farming enterprises, is highly exposed to operational risks due to uncertainty in production, limited managerial capacity, and external environmental factors. Despite this, structured risk management practices such as ISO 31000 are rarely implemented in small agribusiness entities.Purpose: This study aims to identify operational risks, assess their levels based on probability and impact, and formulate appropriate risk mitigation strategies in an agribusiness context, specifically at Alfagro.Design/methodology/approach: This research employs a qualitative descriptive approach supported by risk assessment tools. Data were collected through in-depth interviews, focus group discussions, and questionnaires involving key operational stakeholders. Risk analysis was conducted using the Godfrey risk matrix, while risk treatment strategies were developed based on Flanagan and Norman, aligned with ISO 31000:2018 framework.Findings/Result: The study identifies 13 operational risks categorized into human resources, internal processes, and external factors. The results show that most critical risks are dominated by external (pests and diseases) and process-related issues (storage conditions and harvest delays). One risk is classified as extreme, three as high, five as medium, and four as low. Risk mitigation strategies focus on preventive and reduction measures, particularly in improving post-harvest handling, scheduling, and pest control systems.Conclusion: The implementation of ISO 31000 based risk management is applicable and beneficial for small-scale agribusinesses. Structured risk identification and prioritization enable more effective operational decision-making and improve production sustainability.Originality/value (State of the art): This study contributes to the limited literature on risk management implementation in small-scale agribusiness, demonstrating practical adaptation of ISO 31000 in a youth-based farming enterprise context. Keywords:agribusiness, Alfagro, ISO 31000:2018, operational risk, risk management